PELAKSANAAN TANGGUNG JAWAP PT. NAGA LINE PEKANBARU TERHADAP KESELAMATAN PENUMPANG DARI PEKANBARU TUJUAN SELATPANJANG DARI TAHUN 2018-2019 - Erwin Firmansyah Putra; Maryati Bachtiar; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Sea, river and lake transportation plays an important role to facilitate the transportation of people and goods. In addition, transportation also plays a role as a supporter for the growth of regions that have large natural resources. The emergence of transportation causes the level of traffic accidents of river and land transportation in Indonesia to date is still quite high. In this case, safety is once again the main thing and should be a concern by companies engaged in shipping as done by PT. Naga Line Pekanbaru. This type of research used by the author is sociological legal research, which is a study that examines the legal aspects by looking at applicable laws and comparing them with their implementation in the field by means of surveys. This study was conducted in two locations Pekanbaru and Selatpanjang, while the population and sample are all related parties involved, sources used, primary data, secondary data and tertiary data, data collection techniques in this study by observation, interviews and studies literature. The results of this study are the lack of responsibility carried out by PT. Naga Line Pekanbaru as the transporter in providing security, comfort and safety for passengers. Pursuant to Article 40 Section (1) of Law Number 17 Year 2008 concerning Sailing which essentially asserts that transport companies in the waters are responsible for the safety of passengers and / or the goods they transport. Keywords: responsibility, transportation, passenger safety